GCG, Corporate Characteristics, Financial Distress As A Determinant Of Extensive Voluntary Disclosures - Kartika, Indri; Pramadila, Icca; Indriastuti, Maya (Program Studi Akuntansi FPEB UPI, 2021)
The existence of a conflict of interest between the principal and the agent causes information asymmetry. Information asymmetry is the imbalance of information held between the principal and the agent. This information asymmetry can be minimized by the disclosure of additional information in the annual report, namely by voluntary disclosure. GCG factors, company characteristics, and financial distress are predicted to influence the extensive voluntary disclosure. This study aims to examine the effect of ownership dispersion, financial distress, the board size, CEO duality and age of listings on the extensivevoluntary disclosure. Data population are basic and chemical industry companies listed on the Indonesia Stock Exchange for the 2015-2018. A purposive sampling was used as method and obtained 160 samples. This study used secondary data from annual reports. Data were analyzed by using the Multiple Linear Regression Analysis method. This study found that Ownership Dispersion and Size of the Board of Commissioners have a significant positive effect on Extensive Voluntary Disclosure. Whereas Financial Distress, CEO Duality, and Age of Listing have no significant effect on Extensive Voluntary Disclosure.